(untitled) (Al-Academy, 2020)
Empirical research in the disciplines of art and design has started to escalate and gather consideration within the academic community over the past few decades. However, still, graphic design tends to be a topic extremely under-researched by scholarly persons. Profound research in the field of graphic design extends far beyond the works produced by the designer himself (Khoury, 2009, p.844). In order to develop a clear insight, one needs to delve deep into the subcategories that the diverse field of graphic design is comprised of, including illustration, typography, interaction design, branding and even the impact of notable, eminent institutes from around the world that have taken the budding artists for quite a long time (Walker, 2017). This research paper has been carefully developed for similar purposes. It aims to address the impact of the world-famous Cranbrook Institute on graphic design over these years. It seeks to remove existing gaps of literature by investigating the history and overview of the institute and come up with evidence and conclusions about its successes and downfalls over the period of time.